REACT STRATEGY ON MATHEMATICAL REASONING REVIEWED FROM STUDENTS’ INTEREST IN LEARNING MATHEMATICS - Mahajani, Roy; Abbas, Nurhayati; Djakaria, Ismail; Majid, Majid (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
This study aims to determine whether the REACT strategy effectively enhances students’ mathematical reasoning based on their interest in learning, specifically for students in class X at SMA Negeri 1 Asparaga. The study employed a quasi-experimental with a 2 × 2 treatment-by-level design, analyzed using two-way ANOVA and Tukey’s test. The findings are as follows: (1) The REACT strategy is more effective than conventional teaching methods in enhancing students’ interest in learning (Fcount = 27.230 > Ftable = 4.105) and average scores of 44.79 & 34.52; (2) There is a significant interaction between the teaching model and students’ interest in learning on their mathematical reasoning (Fcount = 7.534 > Ftable = 4.105); (3) Among students with high interest in learning, the REACT strategy outperforms the conventional model, with a significant result (calculated significance with SPSS v.23 = 1.000 > 0.05) and average scores of 57.50 & 44.11; (4) Among students with low interest in learning, the REACT strategy also demonstrates superiority over the conventional model in critical mathematical thinking, with a significant result (calculated significance with SPSS v.23 = 0.314 > 0.05) and average scores of 31.71 & 27.56.